Exact solution of the nonlinear boson diffusion equation for gluon scattering - Möhringer, Louis; Wolschin, Georg (Journal of statistical mechanics: theory and experiment, 2024)
An exact analytical solution of the nonlinear boson diffusion equation is presented. It accounts for the time evolution toward the Bose-Einstein equilibrium distribution through inelastic and elastic collisions in the case of constant transport coefficients. As a currently interesting application, gluon scattering in relativistic heavy-ion collisions is investigated. An estimate of the time-dependent gluon-condensate formation in overoccupied systems through number-conserving elastic scatterings in Pb-Pb collisions at relativistic energies is given.
Gesehen am 19.11.2024